Cultural Scenes and Voting Patterns in Canada. Issue 3 (8th September 2014) - Silver, Daniel; Miller, Diana
Abstract Extending recent social science work using the concept of "scene" into politics, this paper investigates connections between cultural variation and political variation across Canadian localities. First, we introduce the notion of "scene." Then, using a national database of local amenities (with some 1800 categories and 1.6 million data points), we show that key dimensions of cultural meaning account for significant differences in voting patterns in recent Canadian elections. In particular, electoral districts with scenes that suggest themes of self-expression are associated with support for left-leaning parties, while scenes that support locality and corporateness are associated with the right. We conclude with suggestions for pursuing hypotheses about potential mechanisms driving these associations.